The Culture of the Bontoc Igorot - Cawed, Carmencita (Manila : MCS Enterprises, Incorporated, 1972)
This work was first published in UNITAS, a quarterly publication of the University of Santo Tomas, where it appeared in its September, 1965, issue.
Brief history -- The Region, the people and their costumes -- Social organization and dwellings -- Mores and marriage -- Head-hunting, tribal wars, and peace pacts -- Canao, Mangmang and music -- Sickness, death and burial customs -- Properties and inheritance -- Planting, harvest rituals and the Chom-no -- Tengai and superstitious beliefs -- Folklore
Keywords: CULTURE; IGOROT (PHILIPPINES)